Increasing Learning Outcomes in Economics with "Eco Tax" Media for Digital Era Students in Malang, Indonesia - Munir, Syahrul; Putri, Apink Hanestia (KnE Social Sciences, 2024)
This research was carried out on the basis of the use of media that was less than optimal, innovative learning media, and low student learning outcomes, especially during the Covid-19 outbreak at State Senior High School 1 Gondanglegi, Malang Regency. This study aims to develop Android-based ECO-TAX media for the 11th-grade Economics students, majoring in social science, at Gondanglegi 1 Public Senior High School, Malang Regency. The study is expected to improve student learning outcomes. The method used in the study is the ADDIE model research and development (R&D), which comprises five stages, namely (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. Data analysis was carried out quantitatively and descriptively. The results of research and development are in the form of learning media for the Android system in Economics lessons called “ECO-TAX (Economy Tax)”. This media contains materials, learning videos, and learning evaluations, which can be used offline or online by students. The results of the students’ posttest scores showed that there was a striking difference between the learning outcomes of the control class and the experimental class. Android-based ECO-TAX media is effective and feasible to use as an economic learning medium that is proven to be able to improve student learning outcomes. Keywords: learning media, Android, learning outcomes, economics, taxation